Aseptic meningitis rare complication of mumps in an adult - Padmalatha, Kalluru; Sankar, Arumugam; Umashankar, Rajan; Nair, Abhilash; Kanmani, Panneer Selvam (International Journal of Research in Medical Sciences, 2022)
Mumps is endemic worldwide, with epidemics every 3-5 years in unvaccinated populations. After the introduction of the mumps vaccine in the national immunization schedule, the number of reported cases declined by >97% in 1989 until an outbreak of 6584 cases was reported in 2006 even in populations with high-level vaccination coverage and all the patients had a history of vaccination. Here we present a case of mumps with aseptic meningitis in a 42-year-old female. Although historically mumps was a disease of childhood, with most cases occurring in children 5-9 years of age, mumps now most frequently occur in older age groups. This shift in age distribution and the occurrence of mumps in the vaccinated population suggest a waning of vaccine immunity.